Analisis Kebijakan Spasial Dan Peran Kabupaten Puncak Jaya Dalam Wilayah Provinsi Papua - Risnawati K (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2023)
This research is about Spatial Policy Analysis and the Role of Puncak Jaya Regency in the Province of Papua. The main problem is how the spatial policy and the role of Puncak Jaya Regency in supporting the development of the Papua Province region. This problem looks at the spatial policies and the role of Puncak Jaya Regency in the Development of Papua Province, thus this study uses a qualitative descriptive analysis. namely classifying and presenting the data in the form of tables, breakdowns and figures and this analysis was carried out to consider the spatial policies and the role of the Puncak Jaya Regency